Kinematic behavior of southern Alaska constrained by westward decreasing postglacial slip rates on the Denali Fault, Alaska - Mériaux, Anne-Sophie (2012)
Long-term slip rates for the Denali Fault in southern Alaska are derived using 10Be cosmogenic radionuclide (CRN) dating of offset glacial moraines at two sites. Correction of 10Be CRN model ages for the effect of snow shielding uses historical, regional snow cover data scaled to the site altitudes. To integrate the time variation of snow cover, we included the relative changes in effective wetness over the last 11 ka, derived from lake-level records and δ 18O variations from Alaskan lakes. The moraine CRN model ages are normally distributed around an average of 12.1 ± 1.0 ka (n = 22, ± 1σ). The slip rate decreases westward from ∼13 mm/a at 144°49′W to about 7 mm/a at 149°26′W. The data are consistent with a kinematic model in which southern Alaska translates northwestward at a rate of ∼14 mm/a relative to a stable northern Alaska with no rotation. This suggests progressive slip partitioning between the Denali Fault and the active fold and thrust belt at the northern front of the Alaska range, with convergence rates increasing westward from ∼4 mm/a to 11 mm/a between ∼149°W and 145°W. As the two moraines sampled for this study were emplaced synchronously, our suggestion of a westward decrease in the slip rate of the Denali Fault relies largely upon the measured offsets at both sites, regardless of any potential systematic uncertainty in the CRN model ages.